Opportunity and Inequality across Generations - Winfried Koeniger; Carlo Zanella (Center for Economic Studies and ifo Institute (CESifo), 2020)
We analyze inequality and mobility across generations in a dynastic economy. Nurture, in terms of bequests and the schooling investment into the next generation, is observable but the draw of nature in terms of ability is hidden, stochastic and persistent across generations. We calibrate the model to U.S. data to illustrate mechanisms through which nurture and nature affect mobility and the transmission of income inequality across generations, thus complementing the vast empirical literature. To provide a benchmark for the observed status quo, we solve for the social optimum in which the planner weighs dynasties equally and chooses optimal tax schedules subject to incentive compatibility. Analyzing the transition from the calibrated steady state to this social optimum, we find that insurance against intergenerational ability risk increases on the transition path by making welfare of family dynasties more dependent on nurture relative to nature. The insurance comes at the cost of less social mobility. We compare welfare in the social optimum and economies with a simple history-independent tax and subsidy system.
Keywords: E24; H21; I24; J24; J62; 330; human capital; schooling; bequests; asymmetric information; intergenerational mobility; inequality